Bioversity International – Who we are - Bioversity International (2012)
Bioversity International is the only global non-profit research organization that places the use and conservation of agricultural biodiversity in smallholder farming systems at the centre of its work. Our research benefits smallholder farmers in developing countries, most of them living in poverty, who produce 60% of the world’s food.Our research influences policy decisions and investment in agricultural research, from the local level to the global level. From local traditions to global treaties, our work creates new opportunities for economic development, health and sustainability.